Gender Subversion in Kurdish language - Alan Mohammed Awrahman; Farhad Tofiq Hasan; Yara Qadir Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The research sheds light on “Gender Subversion in Kurdish language”, which highlights the dominance of male over language. For this purpose, the research is divided into two chapters; the first covers the theory of genderizing and imposition of male over language: this chapter consists of three sections. In the first section talks about the reasons that lead to linguistic distinction. Then, the second section sex is brought to light as a social/cultural composition, which shows gender is a social and cultural phenomenon and not a biological and genetical one. In the last section of this chapter, linguistic subversion of gender is explained for how the male gender imposes his dominance over speaking and writing in language. As for the second chapter, which is the practical part of this research, illuminates examples of the four linguistic levels; they elucidate the power of male in Kurdish language. For this reason, this chapter comes in four sections. In the first part we pinpoint the dominance of male over language on lexical and dictional level with examples. The second section is dedicated to the dominance of men over language phrases and the cases they appear in with examples. The power of men over sentences and utterances are illustrated in some dominance or subversion circumstances. In the fourth and last section, male dominance over the pragmatic notions is portrayed in the fields they appear in. In the end, we reveal the results we have achieved through the research and then highlighted the references used in the research.